Molecular Symphony of Mitophagy: Ubiquitin-Specific Protease-30 as a Maestro for Precision Management of Neurodegenerative Diseases - Siwach, Ankit; Patel, Harit; Khairnar, Amit; Parekh, Pathik (CNS neuroscience & therapeutics, 2025)
INTRODUCTION: Mitochondrial dysfunction stands as a pivotal feature in neurodegenerative disorders, spurring the quest for targeted therapeutic interventions. This review examines Ubiquitin-Specific Protease 30 (USP30) as a master regulator of mitophagy with therapeutic promise in Alzheimer's disease (AD) and Parkinson's disease (PD). USP30's orchestration of mitophagy pathways, encompassing PINK1-dependent and PINK1-independent mechanisms, forms the crux of this exploration. METHOD: A systematic literature search was conducted in PubMed, Scopus, and Web of Science, selecting studies that investigated USP's function, inhibitor design, or therapeutic efficacy in AD and PD. Inclusion criteria encompassed mechanistic and preclinical/clinical data, while irrelevant or duplicate references were excluded. Extracted findings were synthesized narratively. RESULTS: USP30 modulates interactions with translocase of outer mitochondrial membrane (TOM) 20, mitochondrial E3 ubiquitin protein ligase 1 (MUL1), and Parkin, thus harmonizing mitochondrial quality control. Emerging novel USP30 inhibitors, racemic phenylalanine derivatives, N-cyano pyrrolidine, and notably, benzosulphonamide class compounds, restore mitophagy, and reduce neurodegenerative phenotypes across diverse models with minimal off-target effects. Modulation of other USPs also influences neurodegenerative disease pathways, offering additional therapeutic avenues. CONCLUSIONS: In highlighting the nuanced regulation of mitophagy by USP30, this work heralds a shift toward more precise and effective treatments, paving the way for a new era in the clinical management of neurodegenerative disorders.
Keywords: mitophagy; Parkinson's disease; USP14 inhibitors; Humans; USP30 inhibitors; Alzheimer's disease; deubiquitinating enzymes; Thiolester Hydrolases; lidé; Neurodegenerative Diseases; Precision Medicine; Animals; Mitochondria; zvířata; neurodegenerativní nemoci; Mitochondrial Proteins; ubiquitin‐specific protease; mitofagie; individualizovaná medicína; mitochondrie; mitochondriální proteiny; USP13 inhibitors; thiolesterhydrolasy; Mitophagy